423 – The effects of portulaca oleracea L(purslane) on psychologic symptoms of schizophrenic patients - Parvin, N.; Farzaneh, S.; Rafiee Vardanjani, L.; Goodarzi, I.; Nikfarjam, M. (European psychiatry, 2013)
Despite the availability of an ever-expanding range of typical and atypical antipsychotics, a substantial proportion of patients with schizophrenia show a partial or total lack of response to antipsychotic mono therapy. This study was done to evaluate the effect of purslane on psychologic symptoms of schizophrenic patients. This randomized clinical trial study was carried out on 60 chronic schizophrenic patients in Sina hospital Shahrekord, Iran during 2011-12. Subjects were randomly divided into intervention and control groups. The control group received Risperidone up to 6mg/day and Biperiden 4mg/day for 8 weeks. The Patients in interventional group received 1gr extract of purslane daily with the same regimen for 8 weeks. The scales for assessment of positive symptoms (SAPS) and assessment of negative symptoms (SANS) were recorded in prior and 8th weeks. In addition, CRP and MDA level of patients were assessed in two stage of study. At the end of study, the mean score of positive symptoms were 47.93±18.56 and 57.1±14.83 in intervention and control groups, respectively (P< 0.05), and the mean score of negative symptoms were 40.83±11.03 and 46.13± 9.34 (P< 0.05).The CRP levels of patients in intervention and control groups were .53±.55 and 1.72±.73 at 8 week respectively (P< .05) and the MDA levels were 3.25±1.25 and 5.43± 1.76 respectively (P< .05). According to findings of this study, the use of purslane as an adjunct to Respridone can improve psychological condition of chronic schizophrenic patients and decrease MDA and CRP levels of them.